PENERAPAN REWARD DAN PUNISHMENT DALAM MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM SISWA DI SMKN 4 BONE - Waqiah, Waqiah; Dj, Muhammad Zuhri (Institut Agama Islam Negeri (IAIN) Bone, 2021)
Abstract This thesis discusses how the application of reward and punishment in increasing motivation and learning achievement of Islamic religious education of students at SMK 4 Bone. This research is a qualitative research using three approaches namely the pedagogical approach, psychological approach and theological-normative approach. The data in this study were obtained through primary and secondary data namely observation and interviews directly to Islamic religious education teachers in the study site and also interviews directly to students in SMK 4 Bone by using research instruments in the form of observation guidelines, interview guidelines, documentation and analyzed with data reduction steps, data presentation and conclusion drawer. This study aims to determine the application of reward and punishment in SMK 4 Bone, To find out the forms of the application of reward and punishment in SMK 4 Bone, and to find out the implications of the application of reward and punishment in increasing student motivation and achievement at SMK 4 Bone Results of the research The process of applying rewards and punishments to improve student motivation and learning achievement at SMK 4 Bone, namely teachers and students make a deal that if students do their assignments well and excel will be rewarded. While students who do not do the work, disrupt the teaching and learning process, and do not obey the school rules, get punishment. As for the forms of rewards given to students such as gift giving, praise, body movements such as applause, thumbs up, etc. Whereas the Punishment given can be in the form of reprimands, additional tasks and body language / expressions (such as silence, looking away etc.).